Happiness in Al-Farabi’s Thought: Implications for Islamic Educational Philosophy - Azzahra, Fatimah; Barizi, Ahmad; Rosyidah, Amiliya Nur; Fahmi Fadilah; Zuhro, Fa'izah Darotul (HEUTAGOGIA: Journal of Islamic Education, 2025)
Abstract: This study examines Al-Farabi’s concept of happiness (al-sa‘adah) and analyzes its relevance within the framework of Islamic educational philosophy. The research employs a Systematic Literature Review (SLR) guided by the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework to ensure a rigorous and transparent synthesis. From an initial pool of 1,750 records identified across academic databases such as Google Scholar and ResearchGate, 30 high-quality peer-reviewed studies published between 2000 and 2025 were selected based on strict inclusion criteria. Data were analyzed using manual thematic analysis following the six-stage Braun and Clarke model, with inter-rater reliability validated by two reviewers (Cohen's Kappa > 0.75). The findings indicate that Al-Farabi views happiness as the ultimate aim of human existence, attainable through the perfection of intellect, ethics, and spirituality. True happiness is described not as material prosperity but as a stable inner state achieved through the union of the human intellect with the active intellect (‘aql al-fa‘al). From an educational perspective, this concept underscores the need for a holistic Islamic education model that integrates intellectual development with moral and spiritual cultivation. The study also highlights the implications of Al-Farabi’s Madinah al-Faḍilah, which illustrates that individual happiness is inseparable from a just, ethical, and well-governed society. Nevertheless, this study is limited by its reliance on textual interpretation and the absence of empirical analysis. Future research is recommended to explore the practical application of Al-Farabi’s ideas in contemporary Islamic educational institutions and to examine their impact through empirical or mixed-method approaches.